Polarisation Effects in Above-Threshold Ionisation of Excited Helium. Issue 7 (January 2020) - Bray, A C; Maxwell, A S; de Morisson Faria, C Figueira; Kissin, Y; Ruberti, M; Khokhlova, M; Averbukh, V
Synopsis: We present work on the disentanglement of core dynamics and binding potential influences for Above-Threshold Ionisation in Helium prepared in an excited p state, interacting with a mid-IR field. This was formed by comparing the Coulomb Quantum-Orbit Strong-Field Approximation (CQSFA) with B-spline Algebraic Diagrammatic Construction (ADC) simulations. This may lead to the identification of initial momentum distributions, for tunneling and re-scattering instances, from the CQSFA perspective. The latter method is an inverse approach; thus, the ADC simulations will allow comparison of findings.